Hubungan Antara Ga ya Kepemimpinan Direktur Akper Dan Kompetensi Staf Pengajar Dengan Kinerja Staf Pengajar Akper Rspad Gatot Soebroto Di Jakarta - Memed Sena Setiawan (STIKes RSPAD RSPAD Gatot Soebroto, 2018)
The purpose of the reserch is to study the correlation between principel 's leadership style and teacher competetions with teacher's performance the research l'MS conducted at nursing academica in Jakarta City, Januari 2014.The study involved samples of 40 teacher as responded the study use the total samples.The independent variables invo/,ved in the research -were principal 's leadhership style and teacher's of competentionwhere as the dependent variables was teacher's performance. Findings of the research indicated that they were positive and significant correlation betwean :(1) Principle's leadhership style and teacher peiformance with rx 11 = 0,571 and regression equation Y = 46,546 + 0. 736 X1• (2) Teacher's competention and teacher's performance with rx2y = 0, 608 and regression equation Y = 39,971 + 0,804 ..Y and (3) those two independent variables with teacher performance with rx1x2y = 0,608 and multiple regression equations Y = 39,609 + 0,243xi + 0,562x2.The study implied that the relationship oriented principles leadhership style to ward the teacher should be improved, forthennore teacher's high pe1:formance as teacher get with increased the competations. Keywords: Leadership style, competency, performance, teaching staff.